PENGARUH STRUKTUR MODAL, TOTAL ASSETS TURNOVER, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi Empiris pada Perusahaan Real Estate dan Properti yang Terdaftar di BEI Periode 2013-2016) - Anisqe Adita; Wisnu Mawardi (Faculty of Economics and Business Diponegoro University, 2018)
This study aimed to analyze the capital structure, (DER), Total Asset Turnover (TATO), Liquidity (CR) and Profitability (ROE) that influence the value of the company (PBV), in real estate companies and properties listed on the Indonesia Stock Exchange in 2013-2016. This study measured by Price to Book Value (PBV) which is used as the dependent variable. Then the independent variables used in this study are capital structure (DER), Total Assets Turnover (TATO), Liquidity (CR) with Profitability (ROE) as an intervening variable. The population in this study is all companies in the real estate and property sectors that listed on Indonesia Stock Exchange in 2013-2016. Sampling in this study used purposive sampling which is obtained samples into 32 real estate and property sector companies. The method used is path analysis which is the development of multiple regression and bivariate analysis using the SPSS program. The result of this study indicate that the capital structure (DER) and liquidity (CR) have a negative influence that is not significant to profitability (ROE), then TATO has a significant positive effect on profitability (ROE). This research also shows the results of a positive and insignificant influence on capital structure (DER) and liquidity (CR) on firm value (PBV). Profitability (ROE) and TATO have a positive and significant effect to firm value (PBV). Then profitability is able to mediate the influence of TATO on firm value (PBV), but profitability can’t mediate the influence of capital structure (DER) and liquidity (CR) on firm value (PBV).